Performance optimization of hybrid hydrogen fuel cell-electric vehicles in real driving cycles - Changizian, Sina; Ahmadi, Pouria; Raeesi, Mehrdad; Javani, Nader (PERGAMON-ELSEVIER SCIENCE LTD, 2020)
In this research study, a fuel cell-electric hybrid car is studied. This car includes an electric motor that is connected to a fuel cell and a complex which includes a battery pack and an Ultracapacitor. The assessment of this hybrid vehicle is conducted by using various driving cycles such as FTP-75 driving cycle, NEDC driving cycle and SFTP-SC03 driving cycle. Battery state of charge (SoC) and hydrogen fuel consumption are the effective parameters influencing the vehicle performance. For analysing the performance of this vehicle, an innovative computational model is considered. In this innovative computational model, an accurate control strategy is considered in order to control the power demand, staying the battery packs and the Ultracapacitor state of charge in a limited domain. Results show that in NEDC driving cycle, by means of using Ultracapacitor in this model, 3.3% reduction in fuel consumption and 20.2% decrease in the difference between initial and final State of Charge (SoC) in battery pack can be achieved. In addition, a robust regenerative braking control strategy is used in order to recover some parts of the wasted energy in braking driving modes. (c) 2020 Hydrogen Energy Publications LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: Fuel cell-electric hybrid car; Driving cycles; Vehicle control strategy; Ultracapacitor; Regenerative braking; ENERGY MANAGEMENT STRATEGY; BATTERY; OPERATION; SYSTEM; Chemistry; Electrochemistry; Energy & Fuels